(untitled) (PANGEEA, 2025)
ABSTRACT: Computer graphics, CAAD, e-learning, visualization and virtual reality technologies are increasingly used to communicate the implications of environment understanding and management changes in landscapes and biological systems, well as in national parks and forests. Image-based and data visualization techniques can be used, not only by scientists but also by managers, the public, and desicion-makers, to comprehend massive databases, to interpret dynamic environmental changes, and to evaluate the range of outcomes likely from different management strategies. Recently, however, most developments have been fragmented, the links between different applications regarding learning, understanding and landscape visualization have been few and poor, and the validity and reliability of the visual representations regarding natural (landscape) phenomena have not been tested. This paper introduces (in an initial phase - as a discussion rather than as a well-definedmethod) a coordinated image-based e-learning environment with four modules: landscape data collection, tree modeling, landscape database and landscape data communication, for environment understanding, visualization, real-time interaction and management, and describes four relative goals for tree-based forest visualization with e-learning functionality.